2017
DOI: 10.1177/1941874417733108
|View full text |Cite
|
Sign up to set email alerts
|

Door-to-Needle Time in Acute Stroke Treatment and the “July Effect”

Abstract: Intravenous thrombolysis improves outcomes in acute ischemic stroke in a time-dependent fashion. As in teaching hospitals, clinical outcomes may worsen due to the arrival of new inexperienced house staff early in the academic year (July effect, JE), we evaluated the impact of the "JE" on the door-to-needle time for intravenous thrombolysis and other stroke outcomes. In this retrospective cohort study, we assessed all acute ischemic strokes treated with intravenous thrombolysis between July 2003 and June 2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A quick diagnosis, adequate logistics and rapid response of the stroke team are key determinants of this variable. Due to the demonstrated improvement in clinical results, current guidelines recommend performing at least 80% of rt-Pa treatments within 60 minutes of DTN [13]. DNT provides valuable insight into the course of work in treating stroke and is an indicator of the efficiency of the stroke department.…”
Section: Recombinant Tissue-type Plasminogen Activatormentioning
confidence: 99%
“…A quick diagnosis, adequate logistics and rapid response of the stroke team are key determinants of this variable. Due to the demonstrated improvement in clinical results, current guidelines recommend performing at least 80% of rt-Pa treatments within 60 minutes of DTN [13]. DNT provides valuable insight into the course of work in treating stroke and is an indicator of the efficiency of the stroke department.…”
Section: Recombinant Tissue-type Plasminogen Activatormentioning
confidence: 99%
“…4,5 Other fields that have begun to investigate the possibility of a July effect include gastroenterology, transplant surgery, neurosurgery, cardiothoracic surgery, gynecology, and neurology. [6][7][8][9][10][11] Specifically, within the field of otolaryngology, in patients undergoing head and neck oncologic ablative surgery there was no significant increase in mortality, surgical, or medical complications secondary to the July effect. 12 Similarly, for patients undergoing pituitary skull base surgery, there was no difference in postoperative complications between July and non-July months.…”
Section: Introductionmentioning
confidence: 99%
“…For example, within orthopedic hip fractures, Anderson et al observed a 12% greater relative risk of mortality during July/August, whereas Englesbe et al observed no changes in mortality during resident changeover . Other fields that have begun to investigate the possibility of a July effect include gastroenterology, transplant surgery, neurosurgery, cardiothoracic surgery, gynecology, and neurology …”
Section: Introductionmentioning
confidence: 99%
“…Hence, we read with interest the article “Door-to-needle time in acute stroke treatment and the ‘July Effect’” by Dr Hawkes and colleagues from Argentina in this month’s Neurohospitalist . 2 In a span of over 13 years, they retrospectively studied 101 acute ischemic stroke cases, divided into 3-month intervals, to assess differences between DTNT, thrombolytic-related intracranial hemorrhage, and 3-month outcomes using modified Rankin Scale and National Institute of Health Stroke Scale.…”
mentioning
confidence: 99%
“…This may lead to longer DTNT in July than in other months. Authors cite a 5% reduction in in-hospital mortality for every 15-minute reduction in DTNT 2 but utilized a 1-hour cutoff; perhaps significance would have been achieved with ordinal minutes instead. Worse than DTNT delays, however, would be a missed stroke, untreated with thrombolytic that should have been (ie, due to misread neuroimaging, inaccurately timed onset, misunderstood symptoms, or alternate diagnosis, and so forth).…”
mentioning
confidence: 99%